Predictors of latent reaction speed in athletes: The role of performance level and stress tolerance at different competitive levels - Volgemute, K.; Ulme, G.; Vazne, Z. (Sports Medicine - Open, 2026)
Background Reaction speed represents a fundamental cognitive-motor capacity in sport, yet empirical findings regarding its psychological predictors remain inconsistent, particularly across stages of athletic expertise. This study aimed to investigate the associations of performance level and stress tolerance with latent reaction speed in athletes and to determine whether these associations differ across competitive levels.